2013
DOI: 10.1038/onc.2013.477
|View full text |Cite
|
Sign up to set email alerts
|

PPARβ/δ promotes HRAS-induced senescence and tumor suppression by potentiating p-ERK and repressing p-AKT signaling

Abstract: Peroxisome proliferator-activated receptor-β/δ (PPARβ/δ) inhibits skin tumorigenesis through mechanisms that may be dependent on HRAS signaling. The present study examined the hypothesis that PPARβ/δ promotes HRAS-induced senescence resulting in suppression of tumorigenesis. PPARβ/δ expression increased p-ERK and decreased p-AKT activity. Increased p-ERK activity results from the dampened HRAS-induced negative feedback response mediated in part through transcriptional upregulation of RAS guanyl-releasing prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 66 publications
(83 reference statements)
8
54
0
Order By: Relevance
“…Moreover, knocking down expression of PPARD in TM4 mouse Sertoli cells mitigated these changes in expression of p27, cyclin D1, and cyclin D2. This is consistent with previous findings that ligand activation of PPARD suppresses cyclin D1 or increases p27 expression, causing inhibition of cell proliferation in cancer cells and primary keratinocytes (16,46,47). Furthermore, the present studies also demonstrated that ligand activation of PPARD alters expression of cell cycle regulators by modulating ERK activation in Sertoli cells in vivo and in vitro, consistent with previous studies (16, 48 -50).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, knocking down expression of PPARD in TM4 mouse Sertoli cells mitigated these changes in expression of p27, cyclin D1, and cyclin D2. This is consistent with previous findings that ligand activation of PPARD suppresses cyclin D1 or increases p27 expression, causing inhibition of cell proliferation in cancer cells and primary keratinocytes (16,46,47). Furthermore, the present studies also demonstrated that ligand activation of PPARD alters expression of cell cycle regulators by modulating ERK activation in Sertoli cells in vivo and in vitro, consistent with previous studies (16, 48 -50).…”
Section: Discussionsupporting
confidence: 82%
“…Fluorescence signals were detected using excitation/emission wavelengths of 499/519 or 652/668 nm. All sections were imaged using laser-scanning confocal microscopy as described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with relatively lower H-RAS-induced ER stress and lower p-AKT in H-RAS-expressing wild-type keratinocytes compared with H-RAS-expressing Ppar␤/␦-null cells (11). Similarly, this is consistent with relatively higher H-RAS-induced ER stress and higher p-AKT in H-RAS-expressing Ppar␤/␦-null keratinocytes compared with H-RAS-expressing wild-type keratinocytes (11).…”
Section: H-ras Promotes Er Stress Through P-akt/mtorsupporting
confidence: 76%
“…Senescence-PPAR␤/␦ promotes H-RAS-induced cellular senescence (11). The relatively lower level of ER stress observed in H-RAS-expressing wild-type keratinocytes in the present study correlates with relatively higher levels of senescence previously observed (11).…”
Section: Decreasing Er Stress-associated Upr Increases H-ras-inducedsupporting
confidence: 74%
See 1 more Smart Citation